Determinants of performance in university taekwondo athletes - Do Kim, G.; Pieter, W.; Bercades, L.T. (Science & Sports, 2018)
Objectives: The purpose of this study was to determine the extent to which somatotype and taekwondo experience contributed to performance in varsity taekwondo athletes. Material and Methods: Subjects (38 males, 20.10±1.98years, 170.66±7.17cm, 63.31±11.14kg; 37 females, 19.52±1.80 years, 158.61±5.05cm, 54.16±9.06kg) were athletes competing in a national varsity taekwondo championship. Win-loss records were used as a marker for performance. A Sex x Winners Anova was used to assess differences between men and women by competition result. Results: There was no Sex x Winners interaction for general taekwondo experience (omega2=0.02, 95% CI: 0.00-0.24; power: 0.24), or competition-specific experience (omega2=0.10, 95% CI: 0.00-0.32, power: 0.55), but the effects were not clear. Collapsed over sex, the winners had more general (5.90±2.65 years vs. 2.94±1.90years, d=1.35, 95%: 0.86-1.85) and competition-specific experience (4.95±2.17 vs. 2.52±1.75years, d=1.28, 95% CI: 0.85-1.71). There was no Sex main effect for ectomorphy: 3.055±1.036 for the men vs. 2.386±1.094 for the women: omega2=0.06, 95% CI: 0.00-0.28; power: 0.66 but the effect was also not clear. The effect size for the pairwise comparison was d=0.65, 95% CI: 0.41-0.88. Conclusion: Somatotype in itself may not directly contribute to improved performance, but in combination with general and competition-specific taekwondo experience, it may be facilitated.